Meningkatkan Efisiensi Restoran Cepat Saji dengan Aplikasi Kasir Berbasis Visual Basic - Afriza, Yayang Barru; Negara, Ibtihal Althea Apta; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
In fast food restaurants, transaction management often faces problems such as recording errors and lack of operational efficiency. The purpose of this research is to create a Visual Basic-based cashier application integrated with a MySQL database that enables sales reporting, order tracking, and a more efficient transaction process. Requirements analysis, design, implementation, and testing are steps in the system development process using the Waterfall model. The results show that this application can improve the operational efficiency of fast food restaurants by increasing the accuracy of records and speeding up the customer service process.